2018
DOI: 10.1364/boe.9.002871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflurane anesthesia on physiological parameters in murine subcutaneous tumor allografts measured via diffuse reflectance spectroscopy

Abstract: Diffuse reflectance spectroscopy (DRS) has been used in murine studies to quantify tumor perfusion and therapeutic response. These studies frequently use inhaled isoflurane anesthesia, which depresses the respiration rate and results in the desaturation of arterial oxygen saturation, potentially affecting tissue physiological parameters. However, there have been no controlled studies quantifying the effect of isoflurane anesthesia on DRS-derived physiological parameters of murine tissue. The goal of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…During radiation treatment, mice were kept under anesthesia using a mixture of isoflurane (1.5% v/v) and oxygen while the entire animal body was covered under lead blocks except the tumor. Greening et al have shown this combination and dose to closely mimic no anesthesia conditions [ 22 ]. Mice were monitored daily, and tumors were excised if (1) tumor volume reached 1500 mm 3 (2) tumor necrosis was observed (3) other health related issues occurred.…”
Section: Methodsmentioning
confidence: 99%
“…During radiation treatment, mice were kept under anesthesia using a mixture of isoflurane (1.5% v/v) and oxygen while the entire animal body was covered under lead blocks except the tumor. Greening et al have shown this combination and dose to closely mimic no anesthesia conditions [ 22 ]. Mice were monitored daily, and tumors were excised if (1) tumor volume reached 1500 mm 3 (2) tumor necrosis was observed (3) other health related issues occurred.…”
Section: Methodsmentioning
confidence: 99%
“…30 Bounds for C were set to be the minimum and maximum values for volume fraction. 31 Initial conditions did not affect outcomes as long as they were between the lower and upper bounds. Initial and boundary conditions were constant for all validation phantoms and SDSs.…”
Section: Validation Of Lookup-table Inverse Modelmentioning
confidence: 98%
“…Tumor response [1][2][3][4], antibody expression [5,6], and cell metabolism [7,8] are examples of the different situations where researchers have used longitudinal designs to study some physiological response. Because the frequency of the measurements in a longitudinal study is dependent on the biological phenomena of interest and the experimental design of the study, the frequency of such measurements can range from minute intervals to study a short-term response such as anesthesia effects in animals [9], to weekly measurements would be necessary to enroll more subjects. At the same time, if the excluded observations contain insightful information that is not used, their elimination from the analysis may limit the demonstration of significant differences between groups.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor response 14 , antibody expression 5,6 , and cell metabolism 7,8 are examples of different situations where researchers have used longitudinal designs to study some physiological response. Because the frequency of the measurements in a longitudinal study is dependent on the biological phenomena of interest and the experimental design of the study, the frequency of such measurements can range from minute intervals to study a short-term response such as anesthesia effects in animals 9 , to weekly measurements to analyze a mid-term response like the evolution of dermatitis symptoms in breast cancer patients 10 , to monthly measurements to study a long-term response such as mouth opening following radiotherapy (RT) in neck cancer patients 11 .…”
Section: Introductionmentioning
confidence: 99%